Large scale, unbiased analysis of elementary calcium signaling events in cardiac myocytes. (October 2019) - Tian, Qinghai; Schröder, Laura; Schwarz, Yvonne; Flockerzi, Aline; Kaestner, Lars; Zeug, Andre; Bruns, Dieter; Lipp, Peter
Abstract: The identification of spatiotemporally restricted Ca 2+ signals, Ca 2+ sparks, was instrumental for our understanding of cardiac Ca 2+ homeostasis. High-speed 2D confocal imaging enables acquisition of such Ca 2+ sparks with high-content information but their full appreciation is constrained by the lack of unbiased and easy-to-use analysis tools. We developed a software toolset for unbiased and automatic Ca 2+ spark analysis for huge data sets of subcellular Ca 2+ signals. iSpark was developed to be scanner and detector independent. In myocytes from hearts subjected to various degrees of hypertrophy we acquired >5.000.000 Ca 2+ sparks from 14 mice. The iSpark-enabled analysis of this large Ca 2+ spark data set showed that the highly organized distribution of Ca 2+ sparks present in healthy cells disarrayed concomitant with the development of aberrant transverse tubules and disease severity. Thus, iSpark represents a versatile and universal tool for analyzing local Ca 2+ signaling in healthy as well as diseased, aberrant local Ca 2+ signal transduction. The results from the unbiased analysis of large data sets provide a deeper insight into possible mechanisms contributing to the onset and progression of cardiac diseases such as hypertrophy. Highlights: iSpark for unbiased, automatic analysis of large scale 2D over time Ca 2+ spark data. autonomous 2D assignment of Ca 2+ sparks to RyR clusters. in myocytes from hypertrophied hearts we analyzed >5.000.000 Ca 2+ sparks. the Ca 2+ spark amplitude correlates with the degree of cardiac hypertrophy. the Ca 2+ spark and T-tubular disarray correlate with the degree of cardiac hypertrophy.